Doing God’s Will: Martin Luther King Jr. and the Life of Purpose by Larry L. Macon Sr. (A Book Review) - Kurasz, Weronika (Review of International American Studies, 2021)
Weronika Kurasz's review of Larry L. Macon Senior's Doing God’s Will: Martin Luther King Jr. and a Life of Purpose. Saint Paul Press, 2019.